2017
DOI: 10.1002/cphc.201700425
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Industrial Bimetallic Catalyst Characterization using Scanning Transmission Electron Microscopy and X‐ray Absorption Spectroscopy at One Atmosphere and Elevated Temperature

Abstract: We have developed a new experimental platform for in situ scanning transmission electron microscope (STEM) energy dispersive X‐ray spectroscopy (EDS) which allows real time, nanoscale, elemental and structural changes to be studied at elevated temperature (up to 1000 °C) and pressure (up to 1 atm). Here we demonstrate the first application of this approach to understand complex structural changes occurring during reduction of a bimetallic catalyst, PdCu supported on TiO2, synthesized by wet impregnation. We re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…One of the key challenges for such nanometer-size HEA NPs is in obtaining structural and compositional information at high spatial and temporal resolution, which requires advanced characterization techniques including transmission electron microscopy (TEM). Recently, the development of in situ open-cell and closed-cell environmental TEM with the capability of exposing samples to atmospheric pressure gas environments provides the possibility to study materials behavior under realistic application conditions in real-time. Previous studies have shown that the materials’ behavior under redox reactions can be captured including facet evolution of Pt NPs and PdCu, phase segregation in bimetallic Pt–Ni and PdCu NPs, sintering of Co and Pt, and core–shell NPs .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One of the key challenges for such nanometer-size HEA NPs is in obtaining structural and compositional information at high spatial and temporal resolution, which requires advanced characterization techniques including transmission electron microscopy (TEM). Recently, the development of in situ open-cell and closed-cell environmental TEM with the capability of exposing samples to atmospheric pressure gas environments provides the possibility to study materials behavior under realistic application conditions in real-time. Previous studies have shown that the materials’ behavior under redox reactions can be captured including facet evolution of Pt NPs and PdCu, phase segregation in bimetallic Pt–Ni and PdCu NPs, sintering of Co and Pt, and core–shell NPs .…”
mentioning
confidence: 99%
“…Recently, the development of in situ open-cell and closed-cell environmental TEM with the capability of exposing samples to atmospheric pressure gas environments provides the possibility to study materials behavior under realistic application conditions in real-time. Previous studies have shown that the materials’ behavior under redox reactions can be captured including facet evolution of Pt NPs and PdCu, phase segregation in bimetallic Pt–Ni and PdCu NPs, sintering of Co and Pt, and core–shell NPs . Benefiting from the in situ gas-cell TEM, we studied the high-temperature oxidation behavior of Fe 0.28 Co 0.21 Ni 0.20 Cu 0.08 Pt 0.23 HEA NPs in an atmospheric pressure air environment.…”
mentioning
confidence: 99%
“…The composition profile evidenced a significant reduction of the component D r and a corresponding increase of the component A r at T > 50 °C. By comparing the D r and A r component spectra ( Figure 6 b) with different standards, it is possible to claim that the D r spectrum displayed XANES edge features resembling those of the PdO reference, 57 while the A r spectrum showed features similar to the metallic Pd reference. From the fitting procedure of the Fourier transform (FT) of the EXAFS spectra of the two components D r and A r , the D r is described by two major contributions corresponding to the Pd–O and Pd–Pd coordination shells at distances of 2.03 and 3.06 Å, related to PdO ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…To address this problem, a newer design of in situ atmosphere holder was introduced by Protochips featuring a low-shadowing profiled front blade (Figure 5g,h). In the following study, this special EDS in situ holder was combined with the latest high-efficiency EDS detectors and AC-STEM to observe the behavior of bimetallic nanoparticles at elevated temperature and pressures [88]. The bimetallic catalysts have better performance than monometallic catalysts in activity, selectivity and stability for oxygenate coupling reactions [89][90][91].…”
Section: Improving Eds Signal For Gas Cell Experimentsmentioning
confidence: 99%